Zachowanie autodestrukcyjne = Self-destructive bahavior - Ipatov, Andrei V.; Šišigina, Tat'ana R. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents a systematization and generalization of theoretical views on autodestructive. Discusses the concept of "self-destructive behavior", forms of classification and the place of this phenomenon in the structure of deviance.
Keywords: zachowanie autodestrukcyjne; norma; dewiacje; osobowość; self-destructive behavior; the norm; deviation; personality